Validating Neuro-QoL short forms and targeted scales with people who have multiple sclerosis. (May 2016) - Miller, Deborah M; Bethoux, Francois; Victorson, David; Nowinski, Cindy J; Buono, Sarah; Lai, Jin-Shei; Wortman, Katy; Burns, James L; Moy, Claudia; Cella, David
Background: Multiple sclerosis (MS) is a chronic, progressive, and disabling disease of the central nervous system with dramatic variations in the combination and severity of symptoms it can produce. The lack of reliable disease-specific health-related quality of life (HRQL) measures for use in clinical trials prompted the development of the Neurology Quality of Life (Neuro-QOL) instrument, which includes 13 scales that assess physical, emotional, cognitive, and social domains, for use in a variety of neurological illnesses. Objective: The objective of this research paper is to conduct an initial assessment of the reliability and validation of the Neuro-QOL short forms (SFs) in MS. Methods: We assessed reliability, concurrent validity, known groups validity, and responsiveness between cross-sectional and longitudinal data in 161 recruited MS patients. Results: Internal consistency was high for all measures (α = 0.81–0.95) and ICCs were within the acceptable range (0.76–0.91); concurrent and known groups validity were highest with the Global HRQL question. Longitudinal assessment was limited by the lack of disease progression in the group. Conclusions: The Neuro-QOL SFs demonstrate good internal consistency, test-re-test reliability, and concurrent and known groups validity in this MS population, supporting the validity of Neuro-QOL in adults with MS.